The life cycle of a proverb - Granbom-Herranen Liisa (Portugal, 2026)
The public is often aware of the origin of an expression that becomes an anonymous sentence, then a cliché or a saying and then a proverb. For example, Finnish traditional proverbs include some that originate in fairly recent poetry. However, this is not where the life cycle of a proverb begins. In order to live, a proverb has to be used. For Lauri Honko and Gerard Rooijakkers, the start of the life cycle of a folklore product is in the natural, almost imperceptible past (Honko 2013, 39). It is a stage characterised by authenticity (Rooijakkers 1998, 183). This stage could be called normal everyday life. When thinking about proverbs as artefacts, they do not actually differ from other folklore products as immaterial artefacts.